Las cuatro versiones incunables zaragozanas de las Coplas de Vita Christi de fray Íñigo de Mendoza: estudio lingüístico. - DE BENI, MATTEO (Scripta)
This article offers a linguistic approach to four poetic incunabula versions of the same poetic text, fray Íñigo de Mendoza's Coplas de Vita Christi, published by the Hurus printing house in Saragossa between ca. 1482 and 1495. Firstly, it examines the contribution of Latin and the stereotyped speech of the shepherds in the four incunabula. Secondly, the analysis involves the main graphic, morphosyntactic and lexical aspects of the language of the Coplas de Vita Christi, emphasising the presence of some plural forms of nouns that allow us to link the printed texts, especially the earliest one, with the editio princeps of the text, published by another printer in Zamora.